Strategies for boosting breast milk supply in postpartum women: a scoping review - Nazara, Titin Sundari; Ismarwati (Universitas Gadjah Mada, 2024)
Purpose: This scoping review aims to evaluate the evidence base relating to strategies used to increase breast milk supply in postpartum mothers. Methods: This scoping review adopts the PRISMA-ScR guidelines, which consist of five phases, according to Arksey and O'Malley. They reviewed three databases: Pubmed, Research Rabbits, and ScienceDirect. Inclusion requirements can only be met with full-text, original publications published in English and Indonesian between 2018 and 2022. Results: 30 potentially applicable articles and 10 papers matching the inclusion criteria were found among 644 articles. The four main topics are the impact of soy milk intake, oxytocin massage, breast care, mung bean extract, acupressure treatment, and oxytocin massage and acupressure therapy. Conclusion: The most beneficial therapies for increasing breast milk supply are oxytocin massage and breast care.